SENSE OF PLACE, THE UNIQUE PROPOSITION THAT EMPOWER INTERIOR ARCHITECTURE DESIGN CONSULTANT - Jessica, Bella Eunike; Kusumowidagdo, Astrid (Universitas Ciputra Surabaya, 2024)
The necessity for spatial planning will rise with the population of humans. As a result, the interior business will expand and encounter more rivals where differentiation is required in this industry. The purpose of this research is to determine whether applying the sense of place theme to the interior design consulting business may provide a competitiveadvantage in this industry. Methods of this research were qualitative inquiry, and data was gathered through observations and literature studies. Observations were conducted at various similar consultancies, while literature studies were conducted through textbooks and related journals. Triangulation took place with expert validation in business design. The results supported the conclusions about problems and opportunities. The need for suppliers, other actors in the value chain, and stakeholders is the problem in industry analysis, while the globalization-related problem in market forces separates society into two main groups: those who are more interested in global culture and those who are more interested in preserving and developing local culture. In key trends, it is found that the collapse of regional social and cultural norms in Indonesia is a result of globalization.This problem provides opportunities for interior design consultants who emphasize sense of place theme to have an advantage in this industry. After conducting the industry analysis, there are opportunities to work with related parties who want to develop local culture. Thus the results prove that sense of place has been proven to be a competitive advantage in the interior design consulting business. Keywords: Competitive Advantage, Genius Loci, Interior Design Consultant, Sense of Place.